2016
DOI: 10.1016/j.whi.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Access to Workplace Accommodations to Support Breastfeeding after Passage of the Affordable Care Act

Abstract: Objectives This study examines access to workplace accommodations for breastfeeding, as mandated by the Affordable Care Act, and its associations with breastfeeding initiation and duration. We hypothesize that women with access to reasonable break time and private space to express breast milk would be more likely to breastfeed exclusively at 6 months and to continue breastfeeding for a longer duration. Methods Data are from Listening to Mothers III, a national survey of women ages 18–45 who gave birth in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 24 publications
(27 reference statements)
5
76
0
16
Order By: Relevance
“…All three studies reviewed found that women were twice as likely to breastfeed when there was a private space for lactation. One study found pump breaks resulted in women being twice as likely to breastfeed, whereas a subsequent study found women to be six times as likely to breastfeed with guaranteed pump breaks (Kozhimannil et al, 2016;Tsai, 2013). Workplace policies that support lactation by providing a private space, guaranteed breaks as well as employer and coworker support were consistent themes in all studies reviewed.…”
Section: Facilitators and Barriers For Employed Mothersmentioning
confidence: 80%
See 2 more Smart Citations
“…All three studies reviewed found that women were twice as likely to breastfeed when there was a private space for lactation. One study found pump breaks resulted in women being twice as likely to breastfeed, whereas a subsequent study found women to be six times as likely to breastfeed with guaranteed pump breaks (Kozhimannil et al, 2016;Tsai, 2013). Workplace policies that support lactation by providing a private space, guaranteed breaks as well as employer and coworker support were consistent themes in all studies reviewed.…”
Section: Facilitators and Barriers For Employed Mothersmentioning
confidence: 80%
“…In addition, while the federal law only requires break times up to 1 year, Oregon's policy allows for 18 months, Colorado's for 2 years and New York guarantees this provision for 3 years. Despite passage of the access to workplace accommodations to support breastfeeding, a recent survey of over 500 employed women in the United States reported that only 40% of the women had access to both break time and private space (Kozhimannil, Jou, Gjerdingen, & McGovern, 2016). Those employed women with adequate break time and space were 2.3 times as likely to breastfeed exclusively at 6 months.…”
Section: Workplace Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumes (1) that a workplace is aware of the breastfeeding status of all employees and (2) that it can easily designate space should the need arise. A recent study by Kozhimannil et al (2016) found that only 40% of new mothers who returned to work had access to workplace accommodations for breastfeeding (reasonable break time and private, nonbathroom space). Thus, even if women's orientations to the breastfeeding, mothering, and work relationship are shifting over time, the institutional response continues to lag behind.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of planned behavior (TPB) is often utilized to understand breastfeeding behaviors. [20][21][22][23][24] This theory posits that behavior is directly linked to the intention to perform the behavior. The intention, in turn, is influenced by three direct constructs: attitude, subjective norm, and perceived behavioral control.…”
Section: Introductionmentioning
confidence: 99%